Sosialisasi Isi Piringku : Upaya Pencegahan Stunting Pada Balita dengan Pemanfaatan Daun Kelor - Robawa, Rizki Setyo Putro; Aisah Putri Maharani; Fira Fatma Salsabila; Puspita Dwi Firnanda; Intan Permatasari Fitri Agustine; Putri Amabel Carissa Pradana; Condro Widodo (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The problem of stunting among toddlers in Indonesia is still a big challenge that needs to be addressed immediately. The condition of stunting, which occurs due to a lack of nutritional intake in the womb and a lack of public knowledge about good child rearing patterns, has the potential to disrupt children's physical and cognitive development in the long term. This community service program is carried out with the aim of preventing stunting in toddlers through the socialization of "Fill My Plate" which uses Moringa leaves as a source of nutrition. The socialization was carried out in RW 06, Dukuh Sutorejo Village, Mulyorejo District, Surabaya City, and was attended by pregnant and breastfeeding mothers. The methods used include observation, socialization with presentation of material and cooking demonstrations, as well as implementation evaluation. The results show high enthusiasm from participants and increased understanding of the importance of balanced nutrition in preventing stunting. It is hoped that this program can be expanded to other areas so that more people can benefit from the information provided.